Peran Desain Evaluasi Pembelajaran Dalam Meningkatkan Kualitas Pembelajaran - Nur Hasana Ramadhani; Reyhan Prayudha; Nur Rahma Bone; Zahroddar Zahroddar; Safran Hasibuan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Evaluation of learning is very important to know whether or not a learning system is implemented by educators. Because if an educator does not conduct an evaluation, there is no development in designing a learning system. Educators must create new Innovations to update learning systems that will be implemented in the classroom, ranging from materials, methods, media, learning resources, environments and assessment systems. In designing learning evaluations, educators should also pay attention to the basic principles of evaluation and the requirements that should be considered. The requirements are that the evaluation must actually use the right measuring instrument (Valid) according to its purpose, the test tool must be trusted (Reliabel) or produce the same results (Consistent), and the condition of the evaluation of the latter that is the evaluation must be practical or easy to use does not make it difficult for educators or learners